PENGARUH MEDIA FLASH CARD DALAM PEMBELAJARAN PENDIDIKAN PANCASILA “HAK DAN KEWAJIBAN DIRUMAH DAN DISEKOLAH” TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV DI SEKOLAH DASAR - Dony, Petrus Mau Tellu; Wabang, Yermia S.; Fanpada, Nehemia; Imanuel Yosafat Hadi Manapa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of Pancasila education for fourth-grade students, because teachers do not use varied learning media. The purpose of this study is to determine the Effect of Flash Card Media in Learning Pancasila Education